Toward Intelligent Metasurfaces: The Progress from Globally Tunable Metasurfaces to Software‐Defined Metasurfaces with an Embedded Network of Controllers. Issue 17 (8th July 2020) - Tsilipakos, Odysseas; Tasolamprou, Anna C.; Pitilakis, Alexandros; Liu, Fu; Wang, Xuchen; Mirmoosa, Mohammad Sajjad; Tzarouchis, Dimitrios C.; Abadal, Sergi; Taghvaee, Hamidreza; Liaskos, Christos; Tsioliaridou, Ageliki; Georgiou, Julius; et al.
Abstract: Metasurfaces, the ultrathin, 2D version of metamaterials, have recently attracted a surge of attention for their capability to manipulate electromagnetic waves. Recent advances in reconfigurable and programmable metasurfaces have greatly extended their scope and reach into practical applications. Such functional sheet materials can have enormous impact on imaging, communication, and sensing applications, serving as artificial skins that shape electromagnetic fields. Motivated by these opportunities, this progress report provides a review of the recent advances in tunable and reconfigurable metasurfaces, highlighting the current challenges and outlining directions for future research. To better trace the historical evolution of tunable metasurfaces, a classification into globally and locally tunable metasurfaces is first provided along with the different physical addressing mechanisms utilized. Subsequently, coding metasurfaces, a particular class of locally tunable metasurfaces in which each unit cell can acquire discrete response states, is surveyed, since it is naturally suited to programmatic control. Finally, a new research direction of software‐defined metasurfaces is described, which attempts to push metasurfaces toward unprecedented levels of functionality by harnessing the opportunities offered by their software interface as well as their inter‐ and intranetwork connectivity and establish them in real‐world applications. Abstract : A comprehensive survey of the recent progress in reconfigurable and programmable metasurfaces is provided, tracing their historical evolution from the first globally tunable structures. Subsequently, future research directions toward extra functionality and applicability are described, by proposing software‐controlled metasurfaces incorporating an embedded network of smart controllers with actuation, processing, and sensing capabilities.